Implementasi Sistem Informasi Kehadiran Karyawan di PT Anugerah Alam Konstruksi - Maximilliano, Wesley; Krisna Putra, Jelvin; Yoannita, Yoannita (MDP Student Conference, 2025)
PT Anugerah Alam Konstruksi faces challenges in employee attendance recording, which is still done manually, where field workers submit photos via WhatsApp, while office staff attendance is recorded directly by the admin. This method results in disorganized attendance data and requires more time for processing. To address this issue, an Android and web-based Employee Attendance Information System was designed and developed. This study employs an iterative method, allowing system development to be carried out in stages through multiple cycles. The stages include requirements analysis, system design using an Entity Relationship Diagram (ERD), implementation using Dart for the Android application and PHP for the web administration, as well as system testing and evaluation. The Android application enables employees to clock in based on predefined time and location, while the web-based system facilitates admins in managing, verifying, and compiling attendance reports. The implementation of this system is expected to enhance operational efficiency and company productivity through more accurate and organized attendance recording.